Induced variations of ethyl methane sulfonate mutagenized cowpea (Vigna unguiculata L. walp) plants - Opoku Gyamfi, Muhammed; Eleblu, John Saviour Yaw; Sarfoa, Lawrencia Gyamfi; Asante, Isaac Kojo; Opoku-Agyemang, Frank; Danquah, Eric Yirenkyi (Frontiers in Plant Science, 2022)
Unique variants are desired in the development of genetically improved crops to meet farmer and market needs hence Ethyl Methane Sulfonate (EMS) was used to induce genetic variability in cowpea (Vigna unguiculata cv. Asontem). The optimum concentration (LD50) of EMS for generating the mutagenized population was determined by treating seeds with different concentrations of EMS (0.0%, 0.2%, 0.4%, 0.6% and 0.8% v/v) and observing the germination count after 5 days of plating the seeds in petri dishes. Three thousand cowpea seeds were treated with the 0.4% EMS to generate the M1 and M2 populations that were evaluated for agronomic and morphological traits with untreated seeds serving as control. Data analysis involved distribution of qualitative and quantitative traits. Germination was significantly reduced in the mutagenized population (17.8%) and compared with that of the wild type (61.6%). Percentage survival was significantly higher in wild type (98.38%) as compared with the M1 population (78.46%). Percentage germination in the M2 population (74.03%) was lower than the wild type (80%). A wide spectrum of agro-morphological abnormalities was observed in the M2 population. Wide variations and uniquely different phenotypic classes were observed in leaf colour, leaf shape, growth habit, plant pigmentation, twining tendency, pod curvature, seed shape and seed coat colour. M2 individuals were widely distributed for days to flowering, number of pods per plant, number of seeds per pod, number of locules per pods, percentage seed set, pod length and number of seeds per plant.